"Personal Narrative and Life Course" Revisited: Bert Cohler's Legacy for Developmental Psychology. Issue 145 (September 2014) - Freeman, Mark
Abstract: The primary aims of this concluding chapter are to identify common themes across the preceding chapters, to provide an integrative synthesis of these themes, and to draw out the implications of Bertram Cohler's work for narrative psychology and for the field of developmental psychology more generally. As with the previous chapters, the central ideas explored in Personal Narrative and Life Course remain focal to the discussion. So too is the concept of development, in childhood, adolescence, and beyond. By drawing together the retrospective dimension frequently associated with the idea of narrative with the prospective dimension frequently associated with the idea of development, this chapter also seeks to underscore Cohler's seminal contribution to our understanding of the dynamic movement of human lives in and through time. © 2014 Wiley Periodicals, Inc.